Sarah's key - Rosnay, Tatiana De. (New York : St. Martin's Griffin, 2007)
In modern-day Paris, a journalist finds her life becoming entwined with a young girl whose family was torn apart during the notorious Vel d'Hiv round up, which took place in Paris in 1942. She stumbles upon a family secret which will link her forever to the destiny of a young Jewish girl, Sarah.
English language and literature
DVD; Region 1, NTSC; anamorphic widescreen (2.35:1) presentation; Dolby Digital 5.1 surround.
In English and French, with optional subtitles in English, English SDH or Spanish; closed-captioned.
Keywords: Jews -- France -- Fiction; World War, 1939-1945 -- France -- Anniversaries, etc. -- Fiction; Americans -- France -- Fiction; Family secrets -- Fiction; France -- History -- German occupation, 1940-1945 -- Fiction; Paris (France) -- Fiction; Feature films; Fiction films; Video recordings for the hearing impaired